Role of insect vector Pseudotheraptus devastans in cassava anthracnose disease development - Fokunang, C.N.; Akem, C.; Ikotun, T.; Dixon, A.; Tembe-Fokunang, E.A. (2000)
The aim of this study was to investigate the role of Pseudotheraptus devastans in cassava anthracnose disease transmission and development. P. devastans, Dist (Het. Coriedae) insects were collected from cassava (Manihot esculenta Crantz) field plots at the International Institute of Tropical Agriculture, Ibadan, Nigeria and reared in large cages. The insects were separated at different developmental growth stages of eggs, first to fifth instar nymph, and adults. The different stages of P. devastans showed the presence of Colletotrichum gloeosporioides both externally and internally. Isolates of C. gloeosporioides derived from the insects produced cassava anthracnose disease symptoms (necrotic lesions, wilt and defoliation) 8 weeks after inoculation on two cassava clones. Re-infectivity of cassava plants by the insect-derived fungus established that P. devastans was a potential vector in anthracnose transmission. Except for the first and second instar nymphs, all nymph stages and adult insects produced significant anthracnose symptoms on cassava plants. Defoliation and lesion diameters were greatest using fifth instar nymphs and adult insects. The association between P. devastans feeding and C. gloeosporioides f.sp. manihotis, showed that feeding by P. devastans followed by fungal inoculation and vice versa resulted in more severe anthracnose symptoms than insect feeding or fungal inoculation alone. It was also observed that the influence of P. devastans damage/infection on the development of anthracnose depended on cassava cultivar resistance to both the fungus and the insect feeding.